Psychological Perspectives on Narrative and Storytelling - Beachman, Lisa (Auckland University of Technology, 2018)
Anthropologists identify storytelling as universal feature of human cultures, and theorists in a range of social sciences characterize it as a defining attribute of our species. But despite the fact that psychotherapy is a discipline predicated on sharing stories, relatively little critical attention has been directed at this core human behaviour from within our field. By means of a hermeneutic literature review, this dissertation seeks to identify the conceptions of storytelling and narrative available within psychologically informed research literature, with the intention of forming a basis of understanding for further exploration of the function and uses of narrativity in psychodynamic psychotherapy. My findings suggest that the ability to use narrative effectively is a strong indicator of psychological wellbeing, with implications for both intrapsychic integrity and interpersonal effectiveness. Research moreover suggests that storytelling may be an instinctive human drive with profound implications for our understanding of the world. Thus narrative may also offer insights into how an individual identity is formed, and how it may be transformed within the context of psychotherapy. Current work in the field suggests the importance of further reflection on the epistemological and ethical issues raised by contemporary narrativist conceptions of psychotherapeutic engagement, with implications for both the development of psychodynamic theory and professional practice.
Keywords: Psychotherapy; Narrative; Story; Psychological